Text Mining and Cognitive Psychological Analysis of Sports News in China Daily: The Case of the 2024 Olympics - Kaige Song, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Sports news studies have been an increasingly important area. China Daily’s sports news in English version serves as a window, through which people in English countries can perceive China and the athletes’ images. This paper combines the quantitative method with the qualitative method so that the findings can be more persuasive. This study collects the data from China Daily’s news reports ranging from July 26th, 2024 to August 11th, 2024, and builds a corpus to conduct text mining. The high-frequency word cloud is generated to observe and examine the prominent words. Their diachronic distributions are also explored. By the comparison of British National Corpus (BNC), the top 20 keywords are retrieved to address the prominent meanings. This paper also deals with the collocation analysis of “Chinese” and “athletes”. Based on the reading of the concordance lines and contexts, the meanings of China and its athletes’ images are interpreted. It is found that these pieces of news construct China as a high-tech, progressive, friendly, and forward-thinking image and athletes as a victorious, gracious, and sportsmanlike image. These findings are further interpreted by the qualitatively cognitive psychological analysis. This study has implications for interdisciplinary studies on sports psychology.